Robust Estimation Method for the Economic Subsidies to Educational Institutions in Chile - Vasquez-Perez, O; Davila-Galvez, S (Universidad Politecnica de Valencia., 2023)
In Chile, the Ministry of Education of Chile (MINEDUC) provides resources to the various educational institutions in the country based on a budget estimation model, where the "attendance of students" is the main component to be considered by annual economic subsidies. In the process, this estimation must be computed in the middle of the year, and therefore, the reduction of the impact of error in the estimation face to uncertainty is a desirable goal. In this work, we propose an easy-to-implemented robust estimation method, which is based on the formulation, implementation, and integration of a set of mathematical models that target the minimization of the maximum estimation error. The obtained results show that the proposal obtains a better estimation than the current MINEDUC estimation model, providing an efficient alternative of robust estimation method for the decision makers in the process, exposing insights to be considered in the future. © 2023 International Conference on Higher Education Advances. All rights reserved.